Repairing the Damage: Responsibilities, Obligations, and Systemic Racism in Universities - Lane, Aaron (Problemos, 2025)
The following two claims are commonly accepted: 1) systemic racism has harmed members of ethnic minorities, thus preventing them from achieving appropriate representation on university faculties; 2) university faculty members ought to take steps to ethnically diversify their departments through affirmative action. Here, I consider the following question: assuming that 1) and 2) are correct, who ought to bear the burden of these diversification efforts? I argue that it is implausible that this obligation lies entirely with prospective employees, and that there is some reason to think that at least some existing faculty members have an obligation to engage in what I will call ‘conscientious resignation’: to resign due to a moral obligation to repair systemic racism.
Keywords: Systemic racism; vicarious responsibility; applied ethics; affirmative action